HYDROPONIC TRAINING WITH THE USE OF PLASTIC CUPS AS KALE VEGETABLE CULTIVATION WITH CATFISH CULTIVATION SYSTEM IN BUCKETS - Irsyad, Muhammad Nail; Amelia, Putri Fara; Dhiaulhaq, Ariq; Iqbal, Naufal Fairuz; Oktarina, Nina (Indonesian Journal of Devotion and Empowerment, 2021)
Hydroponic cultivation training activities conducted by students of KKN BMC 1 UNNES 2021 to the community aim to provide knowledge about the use of used plastic cups as a hydroponic medium for the cultivation of kale vegetables. Kale vegetables contain a lot of fibre that has many roles in the digestive process. One of the kale cultivation, kale planting can use used plastic glass media as one form of innovation that can be done to increase public knowledge about simpler vegetable planting as well as to improve people's skills amid the Covid-19 pandemic. Planting kale using used plastic glass media at the same time using a catfish cultivation system in a bucket. The direct benefit of this community service activity is in addition to knowledge, skills, and experience to the community with the use of used plastic cups as an alternative to planting media and buckets as an alternative media for catfish cultivation. This step also aims to increase income and productivity because when the time of harvesting vegetables is also at the same time harvesting catfish so that with this the community gets knowledge and fulfilment of balanced nutrition for families during the Covid-19 pandemic. Kegiatan pelatihan budidaya hidroponik yang dilaksanakan oleh mahasiswa KKN BMC 1 UNNES 2021 kepada masyarakat bertujuan memberikan pengetahuan mengenai pemanfaatan gelas plastik bekas sebagai media hidroponik untuk budidaya sayuran kangkung. Sayuran kangkung mengandung banyak serat yang memiliki banyak peranan dalam proses pencernaan. Salah satu dari budidaya kangkung, penanaman kangkung dapat menggunakan media gelas plastik bekas sebagai salah satu bentuk inovasi yang dapat dilakukan untuk menambah pengetahuan masyarakat mengenai penanaman sayuran yang lebih simpel sekaligus untuk meningkatkan keterampilan masyarakat di tengah masa pandemi Covid-19. Penanaman kangkung menggunakan media gelas plastik bekas sekaligus menggunakan system budidaya ikan lele dalam ember. Manfaat langsung dari kegiatan pengabdian kepada masyarakat ini adalah sebagai tambahan pengetahuan, keterampilan, dan pengalaman kepada masyarakat dengan pemanfaatan gelas plastik bekas sebagai alternatif media tanam dan ember sebagai alternative media budidaya ikan lele. Langkah ini juga bertujuan untuk meningkatkan penghasilan serta produktivitas karena ketika waktu panen sayuran juga sekaligus panen ikan lele sehingga dengan ini masyarakat mendapatkan pengetahuan dan pemenuhan gizi seimbang untuk keluarga selama masa pandemi Covid-19.